"Her sentence is correct, isn't it?": Regulative discourse in English medium classrooms. (October 2019) - Kiramba, Lydiah Kananu; Smith, Patrick Henry
Abstract: Research on discourse in African classrooms has shown the predominance of teacher centered instructional practices. Teacher centered discourse patterns have been blamed for student passivity and disengagement in knowledge production. In this article, we investigate teachers' use of the invariant tag isn't it in Kenyan primary classrooms during ELA and math lessons. Using Bernstein's pedagogical device theory, we submit that the tag plays a regulative function in classroom discourse. Based on our findings, we argue for greater attention to teachers' language choices and discuss implications for classroom discourse practice and research. Highlights: The invariant tag isn't it is a common linguistic feature in World Englishes, including Kenyan English. Teachers across Kenya are familiar with use of isn't it in and outside the context of schooling. We examined use of isn't it in discourse in English medium classrooms. Teachers' use of the invariant tag isn't it regulated classroom discourse and limited dialogue